Gold Catalysis - tandem reactions of diyne-diols and external nucleophiles as an easy access to tricyclic cage-like structures: dedicated to Professor José Barluenga on the occasion of his 70th birthday - Hashmi, A. Stephen K.; Bührle, Miriam; Wölfle, Michael; Rudolph, Matthias; Wieteck, Marcel; Rominger, Frank; Frey, Wolfgang (Chemistry - a European journal, 2010)
Different diyne-diols composed of two terminal homopropargylic alcohol groups were prepared by bi-directional synthesis. Subjection of the syn diastereomers to NAC-gold catalysts (NAC=nitrogen acyclic carbene) in the presence of external nucleophiles such as water or anilines provided substituted and highly rigid heterocyclic cages. The corresponding anti disastereomers polymerised. An intermediate of the reactions of the syn diastereomers could be isolated and even be characterised by crystal structure analysis. Overall, eight new bonds are formed in the reaction, which proceeds by a multistep sequence of highly selective hydroalkoxylations and hydrohydroxylation or hydroaminations. For furyl substituents and for internal alkynes competing reaction pathways could be identified. By the cross-coupling of a product with an iodoaryl substituent, the use of these cage compounds as geometrically defined linking groups by using orthogonal transition-metal-catalysed methodology, namely, gold and palladium catalysis, could be demonstrated.